Analisis Pengaruh Ketimpangan Pembangunan, Pertumbuhan Ekonomi dan IPM Terhadap Kemiskinan di Regional Kalimantan - Nia Destaria br Ginting; Andilopa Ginting (Economie: Jurnal Ilmu Ekonomi, 2023)
This study aims to analyze whether the influence of Development Inequality, Economic Growth and HDI on poverty in Kalimantan. The research method used in this research is Panel Data Regression Analysis Method using Fixed Effect Model (FEM). The type of data used in this research is secondary data. Secondary data can be obtained from the Central Statistics Agency in the Kalimantan Region. The data that has been collected is then carried out with Panel Data Regression Analysis with the Fixed Effect Model where this uses the Chow Test and Husman Test to see the effect of Inequality in Development, Economy and HDI on Poverty in the Kalimantan Region using STATA 16.0 software. The results of the analysis in this study indicate that the influence of Development Inequality, Economic Growth and HDI has a significant effect on Poverty in the Kalimantan Region.